Theory for the negative longitudinal magnetoresistance in the quantum limit of Kramers Weyl semimetals. (23rd November 2018) - Wan, Bo; Schindler, Frank; Wang, Ke; Wu, Kai; Wan, Xiangang; Neupert, Titus; Lu, Hai-Zhou
Abstract: Negative magnetoresistance is rare in non-magnetic materials. Recently, negative magnetoresistance has been observed in the quantum limit of β -Ag2 Se, where only one band of Landau levels is occupied in a strong magnetic field parallel to the applied current. β -Ag2 Se is a material that hosts a Kramers Weyl cone with band degeneracy near the Fermi energy. Kramers Weyl cones exist at time-reversal invariant momenta in all symmorphic chiral crystals, and at a subset of these momenta, including the Γ point, in non-symmorphic chiral crystals. Here, we present a theory for the negative magnetoresistance in the quantum limit of Kramers Weyl semimetals. We show that, although there is a band touching similar to those in Weyl semimetals, negative magnetoresistance can exist without a chiral anomaly. We find that it requires screened Coulomb scattering potentials between electrons and impurities, which is naturally the case in β -Ag2 Se.